γ-2 and GSG1L bind with comparable affinities to the tetrameric GluA1 core - Chenlu Yu; Hendrik F. P. Runge; Antara Mukhopadhyay; Gerd Zolles; Maximilian H. Ulbrich (Cellular & Molecular Biology Letters, 2023)
Abstract Background The AMPA-type ionotropic glutamate receptor mediates fast excitatory neurotransmission in the brain. A variety of auxiliary subunits regulate its gating properties, assembly, and trafficking, but it is unknown if the binding of these auxiliary subunits to the receptor core is dynamically regulated. Here we investigate the interplay of the two auxiliary subunits γ-2 and GSG1L when binding to the AMPA receptor composed of four GluA1 subunits. Methods We use a three-color single-molecule imaging approach in living cells, which allows the direct observation of the receptors and both auxiliary subunits. Colocalization of different colors can be interpreted as interaction of the respective receptor subunits. Results Depending on the relative expression levels of γ-2 and GSG1L, the occupancy of binding sites shifts from one auxiliary subunit to the other, supporting the idea that they compete for binding to the receptor. Based on a model where each of the four binding sites at the receptor core can be either occupied by γ-2 or GSG1L, our experiments yield apparent dissociation constants for γ-2 and GSG1L in the range of 2.0–2.5/µm2. Conclusions The result that both binding affinities are in the same range is a prerequisite for dynamic changes of receptor composition under native conditions.